Preclinical and Toxicology Assessment of ALW-II-41-27, an Inhibitor of the Eph Receptor A2 (EphA2) - Theodore J. Kottom; Kimberly E. Stelzig; Madeline R. Pellegrino; Marc Bindzus; Eunhee S. Yi; Andrew H. Limper (Adis, Springer Healthcare, 2024)
Abstract Background and Objective The EphA2 receptor inhibitor ALW-II-41-27 has proven to be an effective in vitro antagonist of Pneumocystis β-glucan-induced proinflammatory signaling. This suggests its potential as a candidate for initial anti-inflammatory drug testing in the rodent model of Pneumocystis pneumonia (PCP). Methods Initially, single-dose intraperitoneal (IP) injections of ALW-II-41-27 were administered at concentrations of 0, 10, 15, 20, and 30 mg/kg over a 24-h treatment period. Pharmacokinetics were assessed in plasma, bronchoalveolar lavage fluid (BALF), and epithelial lining fluid (ELF). Following these assessments, a final single mg/kg dosing was determined. Mice received daily IP injections of either vehicle or 20.0 mg/kg of ALW-II-41-27 for 10 days, with their weights recorded daily. On day 11, mice were weighed and euthanized. Lungs, liver, and kidneys were harvested for H&E staining and pathology scoring. Lung samples were further analyzed for proinflammatory cytokines using enzyme-linked immunosorbent assay (ELISA) and extracellular matrix production using quantitative PCR (qPCR). Postmortem blood collection was conducted for complete blood count (CBC) blood chemistry analysis. Lastly, ALW-II-41-27 was administered to mice prior to fungal β-glucans challenge to determine in vivo effects on lung inflammation. Results This report describes the PK assessment of ALW-II-41-27 given via IP in C57BL/6 mice. After PK data were generated, we tested ALW-II-41-27 at 20 mg/kg IP in mice and noted no significant changes in daily or final weight gain. ELISA results of proinflammatory cytokines from lung tissues showed no major differences in the respective groups. qPCR analysis of extracellular matrix transcripts were statistically similar. Examination and pathology scoring of H&E slides from lung, liver, and kidney in all groups and subsequent pathology scoring showed no significant toxicity. Blood chemistry and CBC analyses revealed no major abnormalities. Additionally, administering ALW-II-41-27 before intratracheal inoculation of fungal β-glucans, known to induce a strong proinflammatory response in the lungs, significantly reduced lung tissue IL-1β levels. Conclusions In our initial general safety and toxicology assessments, ALW-II-41-27 displayed no inherent safety concerns in the analyzed parameters. These data support broader in vivo testing of the inhibitor as a timed adjunct therapy to the deleterious proinflammatory host immune response often associated with anti-Pneumocystis therapy.